Adaptation to climate change–related ocean acidification: An adaptive governance approach. (15th June 2020) - Greenhill, Lucy; Kenter, Jasper O.; Dannevig, Halvor
Abstract: Climate change-driven ocean acidification (OA) is causing rapid change to global ecosystems and poses a significant threat to marine life. However, predicting ecosystem effects remains highly uncertain and governance responses to OA are not yet forthcoming. Adaptive governance can provide a means to deal with this uncertainty and we consider its application to the polycentric governance of adaptation responses to OA in Scotland, focussing on the aquaculture industry as a vulnerable sector. A workshop was used to develop potential responses to OA and to gain information about present and potential capacity for adaptive governance at national and regional levels. Scottish legislation, policy and planning documents were subsequently analysed to enable description of how governance and management arrangements constrain or enable adaptation responses. Legislative and policy analysis indicates convergence across emerging mechanisms in support of adaptive governance and identified interventions. Recent advances in climate change adaptation in Scotland promotes integration of adaptation into wider Scottish Government policy development and functions, based on iterative and collaborative processes across scales. Alongside this, new models of coastal and marine governance, including a partnership-led regional marine planning process and devolution of seabed management rights under Crown Estate Scotland, seek to advance new models of locally-led and learning-based planning and management which can support adaptation responses. However, adaptation measures at operational scale requires flexibility in the aquaculture licensing regime which is currently of low adaptive capacity. Further, expansion of the industry faces social and ecological constraints which limit spatial measures, and are complicated by uncertainty in predicting local OA effects. Expanding the use of holistic and co-operative management tools such as Aquaculture Management Areas could support adaptation across wider spatial scales. Better integration across policy and planning instruments is also needed to enhance adaptive capacity, including between climate change adaptation, marine planning and aquaculture planning and management. This could be enabled by establishing links between existing and proposed collaborative groups to enhance development of adaptation responses and through co-ordination of monitoring and review processes to promote learning across scales. Highlights: Ocean acidification presents a serious threat to marine aquaculture and food security. Emphasis on locally-led adaptation efforts and local ownership is enhancing adaptive capacity. Co-ordination and coherence is needed to support learning-based adaptation across scales. Legal adaptive capacity of aquaculture licensing and sector constraints may restrict adaptation. Ocean acidification salience is low and limits engaging stakeholders in early adaptation design.